Análise de viabilidade de exportação de veículos antigos para os Estados Unidos - Peruzzo, Gregory Rachelle (My University, 2019)
The following study aims to verify, through the analysis of the export processes, the feasibility of implanting a reselling of old vehicles in the United States. The narrative may provide the reader with an understanding of the processes and variables involved in the export of vintage vehicles. The culture of valuing old cars has spread all over the world, especially in the United States and Europe, and increases the demand for old cars which makes it a business with a high profit potential, besides offering Brazilians and Americans the possibility of having Brazilian classics among others available in the local market. After theoretical basis in the area of export, data collection, market analysis it is possible to affirm that there is demand. With these affirmations we can conclude that exporting vintage collection vehicles is a viable, lucrative business and that there is a viability for the creation of a local business aimed at reaching Americans and Brazilians with a passion for cars.(sic)
O estudo presente tem por objetivo verificar através de análise dos processos de exportação, a viabilidade de revenda de veículos antigos nos Estados Unidos. A narrativa poderá proporcionar ao leitor o entendimento dos processos e variáveis envolvidos no ramo da exportação de veículos antigos. A cultura de valorização dos carros antigos tem se disseminado pelo mundo todo, principalmente nos Estados Unidos e Europa, e faz com que a procura por carros antigos esteja em alta o que o torna um negócio com alto potencial lucrativo além de oportunizar a brasileiros e americanos a possibilidade de ter clássicos brasileiros entre outros disponíveis no mercado local. Após embasamento teórico na área de exportação, levantamento de dados, análise do mercado é possível afirmar que existe demanda. Por este motivo, pode-se concluir que exportação veículos antigos de coleção é um negócio viável, lucrativo e que existe sim a viabilidade para a criação de um negócio local visando atingir americanos e brasileiros apaixonados por carros.(sic)
Keywords: Exportação - Estados Unidos; Automóveis